An Intramolecular Pyranone Diels–Alder Cycloaddition Approach to Cannabinol. Issue 6 (20th March 2014) - Fan, Fangfang; Dong, Jingjing; Wang, Jinqian; Song, Lina; Song, Chuanjun; Chang, Junbiao
Abstract The natural product cannabinol was synthesized using an intramolecular pyranone Diels–Alder cycloaddition reaction as the key step. This strategy is well adapted to access cannabinol analogues. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>